Competencia Emocional y Rendimiento Académico en Estudiantes de Obstetricia de la Universidad Nacional de San Martín - Tarapoto. Diciembre 2013 - Marzo 2014 - Cárdenas Rodas, Erika Rocío (2014)
This research "emotional competence and academic achievement in Students of obstetrics at the National University of San Martín Tarapoto. December 2013 -. March 2014 "is a quantitative prospective explanatory Cross-sectional study, whose main objective is to determine the relationship Between emotional competence and academic performance of students in The professional career of Obstetrics at the National University of San Martin Tarapoto, December 2013 -. March 2014. The data collection instrument was A survey. In the following study participate 213 students registered in these mester Academic 2013. Is determined the emotional competence of participants with Application a quiz of where these results obtained: finding that 64.3% of the Population in study presented an emotional competence in high level- in Other side it found that a 66% get a regular academic performance, be Demonstrate too. That a dimension of the emotional competence is the major Reference with the academic perfomance, it was opportunities search. In conclusion there is a relation ship between emotional competence and Academic performance of students in Obstetrics.